Impact of bone graft harvesting techniques on bone formation and graft resorption: a histomorphometric study in the mandibles of minipigs. Issue 4 (19th February 2014) - Saulacic, Nikola; Bosshardt, Dieter D.; Jensen, Simon S.; Miron, Richard J.; Gruber, Reinhard; Buser, Daniel
Abstract: Background: Harvesting techniques can affect cellular parameters of autogenous bone grafts in vitro . Whether these differences translate to in vivo bone formation, however, remains unknown. Objective: The purpose of this study was to assess the impact of different harvesting techniques on bone formation and graft resorption in vivo . Material and methods: Four harvesting techniques were used: (i) corticocancellous blocks particulated by a bone mill; (ii) bone scraper; (iii) piezosurgery; and (iv) bone slurry collected from a filter device upon drilling. The grafts were placed into bone defects in the mandibles of 12 minipigs. The animals were sacrificed after 1, 2, 4 and 8 weeks of healing. Histology and histomorphometrical analyses were performed to assess bone formation and graft resorption. An explorative statistical analysis was performed. Results: The amount of new bone increased, while the amount of residual bone decreased over time with all harvesting techniques. At all given time points, no significant advantage of any harvesting technique on bone formation was observed. The harvesting technique, however, affected bone formation and the amount of residual graft within the overall healing period. Friedman test revealed an impact of the harvesting technique on residual bone graft after 2 and 4 weeks. At the later time point, post hoc testing showed more newly formed bone in association with bone graft processed by bone mill than harvested by bone scraper and piezosurgery. Conclusions: Transplantation of autogenous bone particles harvested with four techniques in the present model resulted in moderate differences in terms of bone formation and graft resorption.